1992
DOI: 10.1007/bf00180963
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the cellulolytic enzyme system from the brown-rot fungus Coniophora puteana

Abstract: The cellulolytic enzymes of various strains of the brown-rot fungus Coniophora puteana were studied. The organism was grown in an air-lift fermentor in mineral medium containing glucose, cellobiose or amorphous cellulose. The specific growth rate varied between 0.082 and 0.062 h -1. On amorphous cellulose as sole carbon source, the organism secreted various proteins, some of which were characterized. The mixture contained inter alia four endocellulases, two exo-cellobiohydrolases and a cellobiose dehydrogenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 30 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…There is one report of cellobiohydrolase production by Coniophora puteana (33), but this atypical fungus produces laccase activity on wood, and its decay pattern exhibits features of both brown rot and white rot (23). More recent work has shown that crude extracts from wood colonized by two other brown rot fungi, Wolfiporia cocos and Laetiporius sulfureus, were able to release soluble reducing sugars from crystalline cellulose (24).…”
mentioning
confidence: 99%
“…There is one report of cellobiohydrolase production by Coniophora puteana (33), but this atypical fungus produces laccase activity on wood, and its decay pattern exhibits features of both brown rot and white rot (23). More recent work has shown that crude extracts from wood colonized by two other brown rot fungi, Wolfiporia cocos and Laetiporius sulfureus, were able to release soluble reducing sugars from crystalline cellulose (24).…”
mentioning
confidence: 99%
“…The CMCase activity in Clostridium thermocellum decreased 61.5% at 11.1 mM cellobiose [7]. Our derepressed mutant PR-22 held 65% of its xylanolytic activity at 20 mM cellobiose, whereas in microorganisms such as Clostridium stercorarium, 25 mM of this sugar inhibited the cellulase activity by 96% [2]; in Coniophora puteana it decreased by 63% at 6 mM cellobiose [22], and in C. flavigena wt the same activity decreased 92% at 10 mM cellobiose [18]. Cellobiose has been reported to be an inhibitor of cellulase activity in several cellulolytic microorganisms [10].…”
Section: Discussionmentioning
confidence: 83%
“…The factors of brown-rot are brought up as cellulase 16 , nonenzymatic degradation of cellulose and hemicellulose caused by Fenton reaction 2 , biosynthesized oxalic acid 4,17 , and lignin-degrading enzyme 17 . The white-rot fungi possess higher activities of lignin-degrading enzymes (lignin peroxidase, manganese peroxidase and laccase) than brown-rot fungi 13 .…”
Section: Resultsmentioning
confidence: 99%